2011
DOI: 10.1016/s1734-1140(11)70581-3
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole prevents morphine-induced apoptosis in rat cerebral cortex

Abstract: Neuronal apoptosis has been shown to be associated with the development of tolerance to morphine. In the present study, we investigated the effect of intracerebroventricular (icv) administration of an inhibitor of glutamate release, riluzole, on morphine-induced apoptosis in the rat cerebral cortex. Various groups of rats received either morphine (intraperitoneally, ip) and vehicle (icv) or morphine (ip) and different doses of riluzole (icv) once per day for 8 days. An in situ terminal deoxynucleotidyl transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Based on these previous research reports, BP may decrease the expression of BH3‐only proteins to counter against the apoptosis of motor neurons . Consistent with the previous studies, we found that riluzole augmented the level of Bcl‐2 and suppressed the levels of cleaved caspase‐3, Bax, and cleaved PARP, and exhibit antiapoptosis activity . Interestingly, we documented that the expression levels of cleaved PARP and Bax in BP‐treated SOD1 G93A mice were significantly lower than that in riluzole‐treated SOD1 G93A mice (Figure F,H), indicating that regulating apoptosis may become an important action for BP to protect the motor neurons in this mouse model of ALS.…”
Section: Discussionsupporting
confidence: 91%
“…Based on these previous research reports, BP may decrease the expression of BH3‐only proteins to counter against the apoptosis of motor neurons . Consistent with the previous studies, we found that riluzole augmented the level of Bcl‐2 and suppressed the levels of cleaved caspase‐3, Bax, and cleaved PARP, and exhibit antiapoptosis activity . Interestingly, we documented that the expression levels of cleaved PARP and Bax in BP‐treated SOD1 G93A mice were significantly lower than that in riluzole‐treated SOD1 G93A mice (Figure F,H), indicating that regulating apoptosis may become an important action for BP to protect the motor neurons in this mouse model of ALS.…”
Section: Discussionsupporting
confidence: 91%
“…Besides the cytoprotection in the liver and kidney, GGA also exerts protective effects against various stresses in other organs, including the heart and brain (37)(38)(39). The toxicities of morphine in a number of tissues, including the spinal cord and brain, have also been reported (40,41). Whether or not GGA is able to protect against morphine-induced toxicity in other organs remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse model of morphine dependence was created as described in our previous study (29). The mice were injected with escalating morphine doses twice daily (10,20,40,60,80 and 100 mg/kg) for 7 days. Two hours following the last morphine injection, the mice were sacrificed using deep anesthesia, and then heart perfusion was performed using saline.…”
Section: Methodsmentioning
confidence: 99%
“…12 Recent studies have shown that reproductive processes may be influenced by hypothalamic-pituitarygonadal axis via scavenging free radicals. [13][14][15] However, interest in antioxidant has recently been intensified because of their possible effect on egg quality, fertilization, and pregnancy rates. 16,17 Antioxidant therapy has been attended to alleviate infertility, and dietary antioxidant has been beneficial for female reproductive disorder.…”
Section: Introductionmentioning
confidence: 99%